2021
DOI: 10.5009/gnl19275
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Endoscopic Resection for Low-Grade Dysplasia and High-Grade Dysplasia on Gastric Pretreatment Biopsy: Korea ESD Study Group

Abstract: Background/Aims: Some cases of gastric low-grade dysplasia (LGD) and high-grade dysplasia (HGD) on forceps biopsy (FB) are diagnosed as gastric cancer (GC) after endoscopic resection (ER). This study aims to evaluate the clinical outcomes of ER for gastric LGD and HGD on pretreatment FB and to identify the factors that predict pathologic upstaging to GC. Methods: Patients who underwent ER for LGD and HGD on pretreatment FB from March 2005 to February 2018 in 14 hospitals in South Korea were enrolled, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…It was similar to the results of previous studies. 15,[27][28][29][30][31] Sixty-nine point nine percent of HGIN in EFB were diagnosed as EGC in our study, which was comparable to reported results. 30,32,33 It has been found that pathological upgrading was positively correlated with longer operation time and deeper submucosal invasion.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It was similar to the results of previous studies. 15,[27][28][29][30][31] Sixty-nine point nine percent of HGIN in EFB were diagnosed as EGC in our study, which was comparable to reported results. 30,32,33 It has been found that pathological upgrading was positively correlated with longer operation time and deeper submucosal invasion.…”
Section: Discussionsupporting
confidence: 90%
“…15,[27][28][29][30][31] Sixty-nine point nine percent of HGIN in EFB were diagnosed as EGC in our study, which was comparable to reported results. 30,32,33 It has been found that pathological upgrading was positively correlated with longer operation time and deeper submucosal invasion. In addition, the depth of invasion was verified in predicting the risk of nodal metastasis in EGCs.…”
Section: Discussionsupporting
confidence: 90%
“…After successful ablation, the risk of metachronous cancer requires endoscopic surveillance. [183][184][185][186] The timing of endoscopic surveillance is based on the gastritis stage (endoscopy and/or histology).…”
Section: Agreement 100%mentioning
confidence: 99%
“…Most dysplastic lesions occur against a background of high-stage gastritis (OLGA/OLGIM stage III/IV). After successful ablation, the risk of metachronous cancer requires endoscopic surveillance 183–186. The timing of endoscopic surveillance is based on the gastritis stage (endoscopy and/or histology).…”
Section: Wg 2: Diagnosticsmentioning
confidence: 99%
“…Gastric HGD, which has a high predictive value for carcinoma, is recommended to be treated with ER or surgical resection. In 2021, the Korean ESD Study Group reported that Helicobacter pylori infection, smoking history, tumor location in the lower third of the stomach, tumor size >10 mm, pitting lesions, and ulcers were significant predictive factors for prestage diagnosis of EGC in LGD (Jeon et al, 2021). They also reported that previous history of gastric cancer, Helicobacter pylori infection, smoking history, tumor location in the lower third, tumor size >10 mm, pitting lesions, and ulcers were significant predictive factors for a prestage diagnosis of EGC in HGD after ER.…”
Section: Indications For Endoscopic Resectionmentioning
confidence: 99%